LEADERSHIP VALUES IN THE QURAN AS A FOUNDATION FOR THE TRANSFORMATION OF CHARACTER EDUCATION FOR THE DIGITAL GENERATION - Muhammad Rizki Saputra; Abdul Ghofur; Muhammad Sholeh Hasan (LP2M IAI Al-Khairat Pamekasan, 2026)
The rapid development of digital technology has significantly influenced the lives of younger generations, while simultaneously presenting serious challenges to character formation and moral leadership. The digital generation is confronted with information overload, value fragmentation, and identity instability, which demand a more comprehensive and value-based approach to character education. This article aims to explore leadership values embedded in the Qur’an and analyze their relevance as a foundation for transforming character education in the digital era. This study employs a qualitative conceptual approach based on library research, utilizing thematic analysis of Qur’anic verses on leadership as well as classical and contemporary literature in Islamic education and character education. The findings reveal that Qur’anic leadership values—such as tauhid, justice, trustworthiness (amanah), consultation (shura), honesty (shiddiq), wise communication (tabligh), and intelligence (fathanah)—constitute an integrated ethical framework that is highly relevant to addressing moral challenges in digital society. These values function not merely as normative ideals but also as practical moral orientations that guide responsible behavior, ethical awareness, and character development among digital natives. Therefore, Qur’anic leadership can be positioned as a strategic foundation for contextual and sustainable character education aimed at nurturing ethically grounded and transformative leaders in the digital era.